THE CONCEPTION OF HISTORIC SHIPWRECKS OWNERSHIP IN ACCORDANCE WITH INTERNATIONAL LAW - Rachmana, Meike (Indonesian Journal of International Law, 2015)
Technology development pushed forward an access to underwater cultural heritage. Diving tools development makes an access to deeper part of sea accessible. This access not only used by researcher and archeology but also by treasure hunter and historical shipwrecks treasure seekers. These events lead the interested party to explore the sea for valuable things. One of them is historic shipwrecks which contain historical, archaeological or economic value. The significance of this historic shipwrecks leads to an issue about ownership. The ownership claims of historical shipwrecks tis starting to become a global issue after the occurrence of jurisdiction clash among the Flag-state country, Finder, Coastal state, or state origin of the cargo. Therefore, it is important to understand the issue further by exploring the conception on regulation of historic shipwrecks at international level through international convention, at national level through its regulation and practice in several countries and also the regulation and practice in Indonesia.